Factors influencing dignity in sub-Saharan African health systems: a qualitative systematic review - Bald, Sarah MacGregor (Department of Public Health and Family Medicine, 2023)
Dignity, as a basic human right, is demonstrated across numerous leading human rights declarations, covenants, conventions and is reflected in many national constitutions globally. The World Health Organization, along with corresponding United Nations agencies, have also regularly identified dignity as a guiding principle for health systems, service provision, and reform, as dignity is commonly used to measure or achieve quality, person-centred, respectful, and responsive health systems. The prioritization of dignity is argued to improve health outcomes, strengthen professional dignity, and contribute to stronger, more responsive, and rights-based health systems. Yet despite these perceived benefits and the pervasiveness of dignity as a core issue and right, there is a surprising lack of evidence documenting what role dignity has in a health system, for example, whether it influences systems functioning or performance. To address this gap, a qualitative systematic review was conducted in two parts, starting with an initial global scoping review of evidence on dignity in health systems, followed by a systematic review to identify facilitators and barriers to supporting dignity in sub- Saharan African health systems according to the three levels of the health system: interpersonal (micro), organizational (meso), and system-wide (macro). This study found facilitators and barriers to dignity are prominent and present within the health system; and that facilitators and barriers can mainly be viewed as manifestations of prevailing socio-political and health system contexts which shape organizational hardware and software and influence interpersonal engagements between health system actors. For example, national contexts of health care worker shortages and strikes resulted in inadequate staffing levels at facilities, which attributed to decreased supervision, deviations from standards of care, strained professional dignity, and influenced organizational culture normalizing verbal abuse against patients. These contexts ultimately shaped rushed and hostile interactions between a patient and healthcare workers and consequently acted as a barrier to both patient and professional dignity in the health system. Like any system, barriers and facilitators to dignity were closely related to each other and were observed at all levels of the health system. Policy, discrimination, resource availability, organizational culture, staffing and professional dignity, and accountability were re-occurring, and interconnecting factors described as facilitators of and barriers to dignity in SSA health systems. While enabling international guidelines and human-rights declarations, health policy, private, nongovernmental, primary health care (PHC) facilities, birth companions, training, and health care worker resiliency were identified as supportive factors to dignity in health systems, overwhelmingly challenges associated with pervasive discrimination, organizational culture, and structural inadequacies described at health facilities acted as an unequivocal barrier to both patient and professional dignity in sub-Saharan African health systems. This systematic review study confirms that dignity is a critically important issue to health systems and health policy and systems research – but that it is still poorly conceptualized, theorized, or evidenced in relation to how it influences systems functioning and performance.